Cognitive Prerequisites in Development of Childhood Anxiety: An Integrative Literature Review and Thematic Analysis - Behzadpoor, Samaneh; Pouretemad, Hamidreza; Akbari zardkhaneh, Saied (Iranian Journal of Child Neurology, 2022)
It has been suggested that cognitive development affects the emotional experience of children, including anxiety. However, an evidence review is needed to extract cognitive prerequisites that contribute to the development of anxiety in children. The purpose of the study is to explore evidence on cognitive prerequisites involved in experiencing anxiety in children. Four electronic databases of Scopus, OVIDPsycINFO, PubMed, and ScienceDirect were comprehensively searched for 1900 to 2018, yielding 4,618 articles. According to the Preferred Reporting Items for Systematic Reviews and Meta- Analysis (PRISMA) and inclusion and exclusion criteria, 25 articles were found as eligible. The analysis of literature identified 3 themes, including threat perception, future thinking, and generalization. It is suggested that these cognitive abilities may underlie anxiety. These results have important implications for better understanding the effect of cognitive prerequisites in anxiety phenomena and also could shed light on the explanation of anxiety in some disorders characterized by deficits in cognitive development.